ENHANCE SOLUBILITY AND PROLONG RELEASE OF PROCHLORPERAZINE MALEATE USING FLOATING NANOEMULSION IN SITU GEL - Q Almajidi, Yasser; A Albaderi, Ahmed; Fadhel, Hasan (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to prepare floating gastric in situ gel of prochlorperazine maleate (PM) using nanoemulsion technology to improve drug solubility, bioavailability, reduce dosing frequency, and patient compliance. Methods: Eight nanoemulsion formulas (F1â€“F8) of PM were prepared by ultrasonication method using oil, surfactants: cosurfactants (Smix) with different types, concentrations, and ratios, and deionized distilled water. The nanoemulsion formulas were characterized to select the optimum recipe from which six floating in situ gel formulas (floating nanoemulsion in situ [FNI] 1-FNI 6) were prepared using sodium alginate as gelling agent, hydroxypropyl methylcellulose (HPMCK) 4M as rate retarding polymer, calcium chloride as cross-linking agent, calcium carbonate as floating agent, and sodium citrate as buffering and neutralizing gastric acid. All FNI formulas were subjected for the evaluation to assess the formulations suitability concerning the dosage form and intended therapeutic purpose. Results: Formulation variables such as the concentration of sodium alginate, HPMCK 4M, calcium carbonate, and calcium chloride affected the gelling properties, formulation viscosity, floating behavior, and in vitro drug release. Formulation FNI 6 showed acceptable floating lag time (55Â±2.3 s) and >12 h floating duration time, and observe prolong release of the drug in in-situ gelling preparation. Conclusion: The prepared FNI formulas of PM could float in the gastric conditions and released the drug in a sustained manner. The present formulation was enhanced drug solubility with good retention properties and better patient compliance.